2019
DOI: 10.1002/jbt.22349
|View full text |Cite
|
Sign up to set email alerts
|

Has vitamin E any shreds of evidence in cisplatin‐induced toxicity

Abstract: Cisplatin is one of the highly consumed and effective antitumor agents whose clinical application is accompanied by nephrotoxicity adverse reaction. Also, other complications such as ototoxicity and hepatotoxicity are a matter of concern. Today, it is suggested that cisplatin‐associated toxicities are mainly induced by free radicals production, which will result in oxidative organ injury. The evidence is growing over the protective effects of antioxidants on cisplatin‐induced adverse reactions especially nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 109 publications
(277 reference statements)
2
17
0
Order By: Relevance
“…Reduced glutathione level decreased in cisplatin group then increased in all other treated groups to reach the level of control group in a similar way as previously described [21], whereas the increase in lipid peroxide levels in kidney tissues showed a significant increase in the cisplatin positive group as earlier reported [22]. The reactive oxygen species (ROS) such as hydrogen peroxide, superoxide anion, or hydroxyl radicals are normally generated in renal cells and immediately detoxified by endogenous antioxidant (GSH) and catalase unopposed intracellular accumulation of (ROS) leads to membrane lipid peroxidation and (DNA) damage [5,23].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Reduced glutathione level decreased in cisplatin group then increased in all other treated groups to reach the level of control group in a similar way as previously described [21], whereas the increase in lipid peroxide levels in kidney tissues showed a significant increase in the cisplatin positive group as earlier reported [22]. The reactive oxygen species (ROS) such as hydrogen peroxide, superoxide anion, or hydroxyl radicals are normally generated in renal cells and immediately detoxified by endogenous antioxidant (GSH) and catalase unopposed intracellular accumulation of (ROS) leads to membrane lipid peroxidation and (DNA) damage [5,23].…”
Section: Discussionsupporting
confidence: 74%
“…Administration of Vit E alone or in combination with other antioxidant agents could cause amelioration in oxidative stress biomarkers such as decreasing the level of malondialdehyde, reducing serum urea and creatinine, and also enhancing the activities of renal antioxidant enzymes including renal catalase, glutathione-S-transferase, and superoxide dismutase [23]. Although the data from most of the studies are in favors of protective effects of Vit E against cisplatin-induced toxicity, more clinical trials are needed to clarify the clinical importance of Vit E administration as an antioxidant during cisplatin therapy in cancer condition.…”
Section: Discussionmentioning
confidence: 99%
“…Today, it is suggested that cisplatin-associated toxicities are mainly induced by free radicals' production, which will result in oxidative organ injury. The evidence is growing over the protective effects of antioxidants on cisplatin-induced adverse reactions, especially, nephrotoxicity [8][9][10]. The main route for cisplatin elimination is via the kidneys, and around one out of three to four patients treated with full doses of cisplatin could develop renal dysfunction; the percentage could be higher than 50% in children.…”
Section: Cisplatin-induced Toxicitymentioning
confidence: 99%
“…Cell death restriction is also vital for the moderation of severe complications that accompany many other conditions, ranging from oxidative damage, obesity, inflammation, etc. to toxicity of chemotherapeutic agents [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%